2021
DOI: 10.9734/jammr/2021/v33i1130922
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Split-crest Technique with SimultaneousImplant Placement in Atrophic Edentulous Maxillary and Mandibular Bone: A 5-Year Follow-up Study

Abstract: Aim: To evaluate the behavior of the alveolar ridge split technique in a series of surgical cases. Materials and Methods:  One hundred and fifty implants were included in this study for a total of 60 patients. The surgeries consisted of a mid-crestal incision and subsequent bone management with a piezoelectric system. The implants were placed after the alveolar bone was expanded by about 3mm and present bony defects were filled by a mixture of 50% autogenous bone and a xenograft (Bio-Oss®). Bone fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Another study conducted by Guillemant et al, (22) According to bone width, it was found that there was a highly significant increase in bone width (P= <0.0001) after 4 months' assessment which was compatible with Wu et al (12) who reported the mean changes in bone width at the different levels preoperatively, immediately, and 1 year after surgery, as there was a significant increase in ridge width (RW) at all levels revealed an overall mean RW gain of 2.56 ± 1.92 mm after apical U-shaped splitting technique. Similarly, Hamdan et al, (27) and Mahmoud, et al, (19) showed that one stage alveolar ridge splitting technique is more effective and predictable in gaining bone width compared to traditional twostage horizontal grafting technique using autologous bone blocks due to less traumatic effect of avoiding donor site morbidity and avoiding the interruption of oxygenation of the bone segment that results in creating a better bone scaffold for better healing and that short term and long-term survival rates are higher for implants placed in both the maxilla and the mandible when following this technique. According to Starch-Jensen & Becktor (2019) (28) who did a systematic review comparing the ARST with autologous lateral ridge augmentation, an average gain in alveolar ridge width varying between 3.3 to 3.5 mm after maxillary alveolar ridge expansion with the split-crest technique was noticed after 4 months which comes in agreement with our results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study conducted by Guillemant et al, (22) According to bone width, it was found that there was a highly significant increase in bone width (P= <0.0001) after 4 months' assessment which was compatible with Wu et al (12) who reported the mean changes in bone width at the different levels preoperatively, immediately, and 1 year after surgery, as there was a significant increase in ridge width (RW) at all levels revealed an overall mean RW gain of 2.56 ± 1.92 mm after apical U-shaped splitting technique. Similarly, Hamdan et al, (27) and Mahmoud, et al, (19) showed that one stage alveolar ridge splitting technique is more effective and predictable in gaining bone width compared to traditional twostage horizontal grafting technique using autologous bone blocks due to less traumatic effect of avoiding donor site morbidity and avoiding the interruption of oxygenation of the bone segment that results in creating a better bone scaffold for better healing and that short term and long-term survival rates are higher for implants placed in both the maxilla and the mandible when following this technique. According to Starch-Jensen & Becktor (2019) (28) who did a systematic review comparing the ARST with autologous lateral ridge augmentation, an average gain in alveolar ridge width varying between 3.3 to 3.5 mm after maxillary alveolar ridge expansion with the split-crest technique was noticed after 4 months which comes in agreement with our results.…”
Section: Discussionmentioning
confidence: 83%
“…Similar study was evaluated by Wu et al, (14) who investigated a unique apical U-shape splitting method for horizontal bone expansion in undercut areas that was revealed to result in a large increase in bone width at the undercut area of (2.561.92mm) after ridge splitting. Various related studies were also done by Hamdan et al, (27) Abou Hamdan et al, (31) and Agarwal et al, (32) who demonstrated that ridge splitting with implant placement immediately appears to be a less invasive therapeutic option for horizontal alveolar ridge augmentation. The one-stage splitting technique is less time consuming because of no need for second surgery to insert the implant which agreed with Abou Hamdan et al, (31) who found a decrease in healing period in maxilla by three months, with less surgical complications than in the two-stage technique such as detachment of the splitted segment ,possibility of infection due to re-entry and more safe due to direct visualization of splitted segment during the implant insertion.…”
Section: Discussionmentioning
confidence: 94%
“…By reducing the healing period, the ARST offers an important time and financial economy [9], especially regarding the advanced bone resorption in edentulous patients wearing total removable prosthesis for more than 5 years. The ARST seems to be a sure and reliable procedure, the implant success rate was found to be 97.5% [10].…”
Section: Discussionmentioning
confidence: 90%
“…The distance between the two vertical osteotomies is greater on the outer side than on the inner side of the vestibular cortical plate. The osteotomy lines should be traced using the tips progressively in order of size, varying the power level of the characteristics of the incision change too [29]. The tips are used in progression from number one to number five to deepen the osteotomies.…”
Section: Rsp Using Piezosurgerymentioning
confidence: 99%